Interpartner Differences and Governance Mode Dilemma: The Role of Alliance Scope - Tseng,Chiung-Hui (2016)
Abstract It is generally recognized that the governance structure of an alliance, equity versus nonequity, is an important strategic choice. Since an alliance teams up companies that are inevitably divergent in upstream resource endowment and/or downstream market coverage, it is necessary to select an appropriate governance form to manage the interpartner differences and thus facilitate cooperation. Nevertheless, prior studies have suggested conflicting governance modes despite their adherence to the rationale of transaction cost economics. To address this gap in extant literature, the current study takes into account the moderation of alliance scope in the interfirm difference-governance choice linkage. In sum, this paper argues that, to determine a suitable governance structure, there is a need to concurrently examine how different the partnering firms are from each other and what range the collective activities cover. Hierarchical logistic regression analysis was used to test hypotheses in a sample of 125 bilateral alliances. The empirical findings indicate that nonequity modes will be preferred for the alliances that have less interfirm resource disparity and narrower alliance scopes, while equity-based forms will be chosen for the alliances that have less interfirm market divergence and narrower alliance scopes.